The Increase in Children's Independence Through Out Bound Activities for 4-5 Years - Hidayatun Naimah; Purwati; Reza Edwin Sulistryaningtyas (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to determine the increase in children's independence through Out Bound activities for 4-5 years group A in BA. Al-Kautsar TIDAR Islamic Boarding School in Magelang City using the CAR (Classroom Action Research) method. This type uses 2 cycles with stages including planning, implementation, observation and reflection stages. The research subjects were students of group A in BA. Al-Kautsar, totaling 12 children consisting of 5 girls and 7 boys. The data collection method uses non-test in the form of observation. Based on the results of the research and discussion, it can be concluded that the increased independence skills of child A in BA. Al-Kautsar can be improved through circuit games. The increase that occurs can be seen from the research stage, namely observations made during pre-action, implementation of actions in cycle I and cycle II. his is indicated by the results achieved by the subject from the initial conditions or before the increased independence ability action was carried out in the low category. Group A in BA. Al-Kautsar experienced an increase in increased independence skills from pre-cycle by 441,1%, increased in cycle I to 65,9% and increased to 87,2% in cycle II. From these results it can be seen that the increased independence skills of children have reached the success criteria expected by researchers.